RESPON RASA CAMPURAN EKSTRAK SELEDRI (Apium graveolens L.) DAN EKSTRAK ASAM JAWA (Tamarindus indica L.) DALAM SEDIAAN SERBUK EFFERVESCENT - Nutrisia Aquariushinta Sayuti (Fakultas Farmasi Universitas Setia Budi, 2015)
The research aimed to determine effervescent powder formula with concentration variation of Celery extract and Tamarind extracts to the taste aspects of the best. The research was a quasi-experimental design with one shot case study. The evaluation was done to three formula with combination of celery extract and tamarind extract 50%:50% (formula A), 75%:25% (formula B), and 25%:75% (formula C). Physical test was conducted on the organoleptic, moisture content, flow rate, angle of repose and time dispersion of formula. Hedonic test performed to assess the response of the resulting flavor. Respondents of hedonic test was 54 students of Jamu Department, Health Polytechnic Surakarta. The results showed that the different combinations of extract affected to color, aroma and taste parameter of organoleptic results and time dispersion. 61% of respondents liked the flavor of formula C. The flavor of formula A and B was favored by 45% of respondents for each formula. The conclusion was there were no differences of taste respons in the hedonic test results because of differences in theconcentration of combination of celery extract and tamarind extract in effervescent powder formula with p = 0.423 (p> 0.05)